Turkey-Iran Border In The Second World War And Persıan Soldıers Took Refuge In Turkey - Şehitoğlu, Mustafa (Fırat University, 2021)
Turkey-Iran border has been given a structure that gives more importance to refugee transitions and trade cooperation with various agreements made before the Second World War. Some migration movements resulting from Turkey's positive attitude for asylum seekers from Iran, within a program and according to the international law, lasted until the Second World War. Although Iran declared its neutrality in the Second World War, some Iranian soldiers took refuge in Turkey as a result of occupation by the Soviet-British armies. Iranian soldiers appreciating Turkey’s friendly attitude in Iranian border stayed as a guest for a while in Turkey. This study examined various documents describing security measures and cooperation developed by Turkey over the Iranian border before and during the Second World War. In addition, it investigated Iranian soldiers who took refuge in Turkey as well as a letter of thanks in archival documents providing information about the Iranian border of Turkey.

Türkiye-İran sınırı, İkinci Dünya Savaşı öncesinde yapılan çeşitli anlaşmalar ile nüfus geçişleri ve ticari işbirliğine daha fazla önem veren bir yapıya kavuşturulmuştur. Türkiye’nin İran’dan gelen sığınmacılar için bir program dâhilinde ve devletler hukukuna göre geliştirdiği olumlu tavrı sonucunda oluşan bazı göç hareketleri, İkinci Dünya Savaşına kadar sürmüştür. İran’ın, İkinci Dünya Savaşında tarafsızlığını ilan etmesine rağmen, Sovyet-İngiliz orduları tarafından işgal edilmesi neticesinde, dağılan İran ordusundan bir kısım asker de Türkiye’ye sığınmıştır. Türkiye’nin İran sınırında ortaya koyduğu dostça yaklaşıma teşekkür eden İranlı askerler, bir müddet Türkiye’de misafir olarak kalmışlardır. Bu çalışma, İkinci Dünya Savaşı öncesi ve savaş sırasında, Türkiye’nin, İran sınırında geliştirdiği güvenlik ve işbirliği tedbirlerini anlatan birkaç belge ışığında ele alınmıştır. Ayrıca Türkiye’ye sığınan İranlı askerler ile Türkiye’nin İran sınırı hakkında bilgi veren arşiv belgelerinde mevcut bir teşekkür mektubu incelenmiştir.
İKİNCİ DÜNYA SAVAŞINDA TÜRKİYE-İRAN SINIRI VE TÜRKİYE’YE SIĞINAN İRANLI ASKERLER